1999
DOI: 10.1034/j.1398-9995.1999.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial hyperresponsiveness and airway wall remodelling induced by exposure to allergen for 9 weeks

Abstract: Prolonged exposure to allergen has been proposed to be important for the development of bronchial hyperresponsiveness and airway remodelling in asthma. The present study was designed to examine the effect of chronic allergen exposure on bronchial responsiveness, eosinophil infiltration, and airway remodelling. We sensitized brown Norway rats with the occupational allergen trimellitic anhydride (TMA) and exposed the animals to TMA conjugated to rat serum albumin (TMA-RSA) on 5 consecutive days each week for 9 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
2

Year Published

2001
2001
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
1
20
2
Order By: Relevance
“…In asthma, thickening of airway smooth muscles may lead to narrowing of the airways [19], and thus contribute to nonspecific AHR. This mechanism was postulated to be true in previous experiments, which used BN rats treated in a way similar to the present experiment [4,5]. Contrary to the present authors9 expectation, however, the morphological changes of the airways observed after 1 month of antigen challenges disappeared after 3-month repeated antigen challenges; and there were no significant differences in the morphology of the airways between the repeatedly antigen-challenged rats and the control rats.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In asthma, thickening of airway smooth muscles may lead to narrowing of the airways [19], and thus contribute to nonspecific AHR. This mechanism was postulated to be true in previous experiments, which used BN rats treated in a way similar to the present experiment [4,5]. Contrary to the present authors9 expectation, however, the morphological changes of the airways observed after 1 month of antigen challenges disappeared after 3-month repeated antigen challenges; and there were no significant differences in the morphology of the airways between the repeatedly antigen-challenged rats and the control rats.…”
Section: Discussioncontrasting
confidence: 56%
“…In the same strain of rats, multiple antigen challenges are reported by some investigators to develop chronic abnormalities resembling those in asthma, such as airway remodelling [4,5]. In addition, it has been demonstrated that nonspecific AHR occurs after multiple antigen challenges in some reports [4][5][6][7][8]. In contrast, there have been a number of studies, which observed the generation of IgE isotype-specific tolerance [9,10] after multiple antigen challenges and also the attenuation of antigen-specific AHR.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In sharp contrast, other studies have documented persistent airway eosinophilia (10,11). With respect to Igs, it has been shown in one study that prolonged exposure leads to persistent IgE production (11), while in another, prolonged exposure leads to transient IgG and IgE expression (9). While these discrepancies may reflect differences in the experimental models, our observations demonstrate that, in the mouse, chronic exposure to Ag does not a Mice were exposed to OVA in the context of GM-CSF for 2 or 4 wk.…”
Section: Discussionmentioning
confidence: 72%
“…This understanding is further limited by the fact that research examining the effect of chronic allergen exposure on airway inflammation has produced controversial results. Studies showing that chronic allergen exposure does not lead to persistence of airway inflammation (8,9) suggest that allergen alone is insufficient in perpetuating the inflammatory response. Others have documented persistent airway eosinophilia (10,11); however, the focus of these studies was on airway remodeling and lung physiology rather than on immune inflammatory processes.…”
Section: Chronic Exposure To Innocuous Antigen In Sensitized Micementioning
confidence: 99%